2008
DOI: 10.1073/pnas.0805757105
|View full text |Cite
|
Sign up to set email alerts
|

The bacteriophage λ Q antiterminator protein contacts the β-flap domain of RNA polymerase

Abstract: The multisubunit RNA polymerase (RNAP) in bacteria consists of a catalytically active core enzyme (␣ 2␤␤ ) complexed with a factor that is required for promoter-specific transcription initiation. During early elongation the stability of interactions between and core decreases, in part because of the nascent RNA-mediated destabilization of an interaction between region 4 of and the flap domain of the ␤-subunit (␤-flap). The nascent RNA-mediated destabilization of the region 4/␤-flap interaction is required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 34 publications
4
70
0
Order By: Relevance
“…We therefore wanted to identify amino acid substitutions within the flap-tip helix that weakened the AsiA/␤-flap interaction, but did not prevent recognition of Ϫ10/Ϫ35 promoters. We tested the effects of several previously characterized amino acid substitutions in the ␤-flap-tip helix (31) and found that substitution G907K moderately disrupted the AsiA/␤-flap interaction, and amino acid substitutions I905A and F906A in combination strongly disrupted the AsiA/␤-flap interaction (Fig. 3 E and F).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore wanted to identify amino acid substitutions within the flap-tip helix that weakened the AsiA/␤-flap interaction, but did not prevent recognition of Ϫ10/Ϫ35 promoters. We tested the effects of several previously characterized amino acid substitutions in the ␤-flap-tip helix (31) and found that substitution G907K moderately disrupted the AsiA/␤-flap interaction, and amino acid substitutions I905A and F906A in combination strongly disrupted the AsiA/␤-flap interaction (Fig. 3 E and F).…”
mentioning
confidence: 99%
“…Prior work has established that the ␤-flap-tip helix (␤ residues 900-909) is the primary determinant of the 70 region 4/␤-flap interaction (30) and that removal of the ␤-flap-tip helix eliminates any detectable interaction between 70 region 4 and the ␤-flap in the 2-hybrid assay (31). We found that removal of the ␤-flap-tip helix also eliminated the interaction between AsiA and the ␤-flap ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The antitermination activity of N and Q, but not gp39, is enhanced by cell-encoded proteins, including transcription elongation factor NusA, which by itself stimulates termination but reverses its activity to additionally stabilize the TEC in cooperation with N and Q (5, 6). Curiously, the N, Q, gp39, and NusA proteins all target the flexible β flap domain of RNAP (2,4,(7)(8)(9)(10)(11) that forms a part of the RNA exit channel and has been implicated in intrinsic termination and transcription pausing through direct interaction with RNA hairpins (Fig. 1) (3,(12)(13)(14).…”
mentioning
confidence: 99%
“…56 Q becomes a subunit of RNA polymerase at the s70-dependent pause site at C16 described above, where a DNA binding site for Q is exposed. 66,67 The primary activity of Q relevant to the mechanism of antitermination is that binding of Q to the paused RNAP drives it out of the pause; 68,69 thus, the Q modification must counteract the pausing element, which we know is an EPS. Since an EPS also likely underlies the function of terminators, such antipausing may constitute the essential act of antitermination.…”
Section: λ Q Antiterminationmentioning
confidence: 99%